Comparative Study of Screen Printed Electrodes for Ammonia Gas Sensing in Ionic Liquids - Murugappan, K.; Lee, J.; Silvester, Debbie (Elsevier Inc., 2011)
Commercially available screen printed electrodes (SPEs) have been used for electrochemical ammonia (NH3) gas sensing in the room temperature ionic liquid 1-ethyl-3-methylimidazolium bit(trifluoromethylsulfonyl)imide ([C2mim][NTf2]). The SPEs consist of a 4mm diameter working electrode surface (carbon, platinum or gold) with a silver reference and C/Pt/Au counter electrode. No obvious voltammetric response was observed for NH3 oxidation on the carbon SPE, however, clear oxidation peaks were observed on Pt and Au. Linear calibration graphs were obtained for oxidation peak current vs. concentration in the range 240-1360ppm NH3 on both Pt and Au SPEs, giving limits of detection of 50ppm and 90ppm, respectively. The voltammetry on Au was complicated by additional peaks (most likely due to water impurities in the RTIL), which leads us to suggest that Pt is the preferred electrode surface material. The conditions of the experiment were chosen to be as close to real conditions as possible (no pre-vacuuming of the RTIL and no polishing/electrochemical cleaning of the SPE surface before experiments) suggesting that Pt SPEs in conjunction with non-volatile RTILs may provide cheaper alternative sensing materials compared to those currently used in commercial amperometric gas sensing devices.